Effects of strength training on physical fitness and sport-specific performance in recreational, sub-elite, and elite rowers: A systematic review with meta-analysis - Thiele, D.; Prieske, O.; Chaabene, H.; Granacher, U. (Journal of Sports Sciences, 2020)
The purpose of this systematic review with meta-analysis was to examine the effects of strength training (ST) on selected components of physical fitness (e.g., lower/upper limb maximal strength, muscular endurance, jump performance, cardiorespiratory endurance) and sport-specific performance in rowers. Only studies with an active control group were included if they examined the effects of ST on at least one proxy of physical fitness and/or sport-specific performance in rowers. Weighted and averaged standardized mean differences (SMD) were calculated using random-effects models. Subgroup analyses were computed to identify effects of ST type or expertise level on sport-specific performance. Our analyses revealed significant small effects of ST on lower limb maximal strength (SMD = 0.42, p = 0.05) and on sport-specific performance (SMD = 0.32, p = 0.05). Non-significant effects were found for upper limb maximal strength, upper/lower limb muscular endurance, jump performance, and cardiorespiratory endurance. Subgroup analyses for ST type and expertise level showed non-significant differences between the respective subgroups of rowers (p = 0.32). Our systematic review with meta-analysis indicated that ST is an effective means for improving lower limb maximal strength and sport-specific performance in rowers. However, ST-induced effects are neither modulated by ST type nor rowers` expertise level.